Analysis of the Merger and Acquisition of PT GOTO (Gojek 0 Tokopedia) Tbk: Share Valuation and Firm Financial Performance - Kendra , Abigail; Fauzi, Fitriya (International Journal of Business, Management and Economics, 2024)
Mergers and acquisitions have become business practices to improve shareholder welfare. One of the newest phenomena in Indonesia is the merger of two large companies, namely Gojek, a transportation service provider, and Tokopedia, an e-commerce platform. This merger occured in 2021 with the official name PT GOTO Gojek – Tokopedia Tbk. When conducting an Initial Public Offering (IPO), the share price of PT GOTO Gojek – Tokopedia Tbk was set at Rp. 338 per share (CNBC, 2022). Many hopes were pinned on the share price, but the share price of PT GOTO Gojek – Tokopedia Tbk did not match expectations. In December 2023, based on the IDX website, the share price of PT GOTO Gojek – Tokopedia Tbk has dropped drastically to Rp. 95, experienced a decrease of Rp. 243 since IPO. This research shows whether the merger decision of the two companies has an effect on their intrinsic value as well as their liquidity ratio, activity ratio, solvability ratio and profitability ratios.